Microplastics and exercise: impacts on performance and physiological health - Jiao, Xianwei; Cao, Qinglei; Deng, Zhongyuan (Frontiers in Sports and Active Living, 2025)
Microplastics, a widespread and growing environmental pollutant, have raised global concerns due to their pervasive presence in both urban and natural environments. The extensive use of plastics has led to human exposure through inhalation, ingestion, and skin contact, posing potential risks to athletes and fitness enthusiasts during exercise. Studies suggest microplastics may impair exercise performance and health, though research remains limited. Current evidence indicates microplastics enter the body via respiration, water, and food, potentially disrupting physiological functions. However, their exact mechanisms, exposure thresholds, and long-term effects on athletic performance are poorly understood. This paper reviews microplastic sources, exposure pathways in sports, and their physiological impacts, aiming to establish a comprehensive understanding of their role in exercise science. By analyzing existing literature, this study explores microplastics’ influence on physical function, athletic performance, and training outcomes. The findings may help identify actionable prevention strategies, promoting safer sports environments. Further research is needed to clarify microplastics’ health implications and develop effective mitigation measures for athletes.